2018
DOI: 10.1186/s12966-018-0725-x
|View full text |Cite
|
Sign up to set email alerts
|

Eating behavior and body composition across childhood: a prospective cohort study

Abstract: BackgroundAlthough many cross-sectional studies reported that children with overweight or obesity show more food approaching and less food avoidant eating behaviors, there is a lack of replication in longitudinal studies. Therefore, the question remains whether healthcare professionals should target eating behaviors in childhood obesity interventions and prevention. We aimed to examine the longitudinal and possible bi-directional associations between eating behavior and body composition across childhood.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 43 publications
10
56
2
2
Order By: Relevance
“…In the same cohort, Derks et al 4 showed that emotional overeating was both a predictor and consequence of higher weight status from 4 to 10 years, yet these factors were not cross‐sectionally associated at 4 years. Associations between emotional overeating and weight may be age‐dependent, emerging with children's increasing autonomy and access to foods 4 or adiposity rebound 14 . This may explain our non‐significant association between emotional overeating and weight status in younger children.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the same cohort, Derks et al 4 showed that emotional overeating was both a predictor and consequence of higher weight status from 4 to 10 years, yet these factors were not cross‐sectionally associated at 4 years. Associations between emotional overeating and weight may be age‐dependent, emerging with children's increasing autonomy and access to foods 4 or adiposity rebound 14 . This may explain our non‐significant association between emotional overeating and weight status in younger children.…”
Section: Discussionmentioning
confidence: 98%
“…Emotional and behavioral problems in 3 year old Dutch children predicted increasing trajectories of emotional overeating from the ages of 4 to 10 years 36 . In the same cohort, Derks et al 4 showed that emotional overeating was both a predictor and consequence of higher weight status from 4 to 10 years, yet these factors were not cross‐sectionally associated at 4 years. Associations between emotional overeating and weight may be age‐dependent, emerging with children's increasing autonomy and access to foods 4 or adiposity rebound 14 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…accrual method) for future studies about this topic in order to improve the quality of the data and the reliability of analysis (World Health Organization, 2011). Third, the sample was no probabilistic and relatively smaller and less homogenous than the samples used in research studies conducted in other countries such as Netherlands (Derks et al, 2018), United Kingdom (Brown & Lee, 2015) and even in Hispanic nations (Falcão et al, 1991;Reyes et al, 2014;World Health Organization, 2012). This methodological issue may lead to inconsistent results and may limit the generalization of the results.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Eating behaviors such as food responsiveness and satiety responsiveness are associated with weight status (French et al, 2012). In fact, a predictive study conducted in the Netherlands concluded that children who have higher BMI tend to show more food responsiveness and less satiety responsiveness (Derks et al, 2018). In this study, satiety responsiveness is defined as the child's ability to recognize and adjust their food intake considering their physiological cues and their internal perception of satiety during and after the act of eating (Birch et al, 2001;Brown & Lee, 2015;Llewellyn et al, 2008;Obregón et al, 2014;Sinopolou et al, 2015).…”
Section: Association Among Eating Behaviors Bmi and Breastfeedingmentioning
confidence: 99%